Factores de riesgo de hipotiroidismo primario en pacientes afiliados al IESS del Centro de Salud San Pedro de Vilcabamba de Loja - Cumbicos Ortega, José Manuel (2021)
Hypothyroidism is considered one of the worldwide thyroid diseases with disability and morbidity, it presents itself with nonspecific symptoms, and entails complications due to the lack of an early diagnosis and adequate treatment. The purpose of the present study was to determine the prevalence of hypothyroidism, to identify the predisposing risk factors for this pathology and to establish the relationship of the risk factors with the sex and the age of the patients treated in 2019 at the IEES San Pedro de Vilcabamba Hospital. This is a descriptive and cross-sectional study with a quantitative approach. The information was collected through the application of an instrument to 42 hypothyroidism diagnosed patients, through a home visit. The following results were obtained: prevalence with a greater frequency from the age of 66 years onwards with 42.85% (n = 18) prevailing in the female sex with 83.33% (n = 35). The risk factors found were a family history of hypothyroidism with 35.7% (n = 15); personal history of thyroidectomy 7.20% (n = 3); consumption of salt in grain 11.90% (n = 5); consumption of piped water 28.58% (n = 12); and consumption of goitrogens in 100%. When establishing the relationship between risk factors with sex and age, it was determined that female patients with an age range over 65 years have a greater predisposition to present primary hypothyroidism. It is concluded that, the female sex, and the age of 61 years onwards, are the risk factors with greater relevance for the development of this pathology. Key words: Hypothyroidism, family history, female sex